Comparison of Sesamol and its Liposomal Nanocarrier in the Quest for Anti-Metastatic Agents in Colorectal Cancer Cell Line HT-29 (Medical Forum Monthly, 2023)
Objective: To evaluate the effects of sesamol alone and its liposomal nanocarriers in inhibiting the migratory potential of colon cancer cell line (HT- 29).Study Design: Experimental StudyPlace and Duration of Study: This study was conducted at the Department of Molecular Medicine, Ziauddin University, Clifton Campus, Karachi from October, 2022 to July, 2023.Materials and Methods: The anti-migratory effects of sesamol, sesamol loaded liposomal nanocarriers and 5-Flourouracil on CRC cell line was evaluated through scratch assay, cells were seeded in 6 well plate and a wound was introduced using 10ul pipette tip on the layer of cells. The cells were then treated with compounds and observed under inverted microscope at different time intervals (0, 24, 48, 72 and 96 hours). Images were captured and the wound closure area was analyzed using image J software.Results: The results of our study revealed that sesamol and its liposomal nanocarriers showed highly significant reduction in wound healing with p-value (<0.0001) up till 96 hours. While 5-FU has shown very highly significant results till 48 hours with p-value of (<0.0001) and after which it showed complete cytotoxicity.Conclusion: Current study depicted significant anti-migratory effects of sesamol and its liposomal nanocarriers in CRC cell line HT-29, suggesting their anticipated role in impeding the metastasis of colorectal cancer.